Glucagon like peptide-1 receptor agonists may ameliorate the metabolic adverse effect associated with antiretroviral therapy. (September 2016) - Culha, Mehmet Gokhan; Inkaya, Ahmet Cagkan; Yildirim, Emre; Unal, Serhat; Serefoglu, Ege Can
Abstract: The number of people living with HIV and AIDS (PLWHA) reached to almost 40 million, half of which are under antiretroviral treatment (ART). Although the introduction of this therapy significantly improved the life span and quality of PLWHA, metabolic complications of these people remains to be an important issue. These metabolic complications include hyperlipidemia, abnormal fat redistribution and diabetes mellitus, which are defined as lipodystrophy syndrome. Glucagon-like peptide-1 (GLP-1) is a neuropeptide secreted from intestinal L cells and recently developed GLP-1 receptor agonists (GLP-1RAs) stimulate insulin secretion, improve weight control and reduce cardiovascular outcomes. This class of drugs may be a valuable medication in the treatment of HIV-associated metabolic adverse effects and extend the life expectancy of patients infected with HIV.